Screening of several microalgae revealed biopesticide properties of Chlorella sorokiniana against the strawberry pathogen Phytophthora cactorum - Jokel Martina; Salazar João; Chovancek Erik; Sirin Sema; Allahverdiyeva Yagut (SPRINGER, 2025)
Present agricultural production typically depends on the intensive use of synthetic pesticides with potentially harmful consequences for humans and the environment. To ensure food security for the rapidly rising global population it is necessary to develop more sustainable alternatives to synthetic pesticides. Microalgae possess a large diversity in antimicrobial compounds and are considered one of the most promising sustainable sources of novel biopesticides. Antimicrobial activities of 15 microalgae strains were investigated against a selection of seven common plant pathogens relevant to agricultural production. Several microalgae were identified posessing antimicrobial activity, with an extract of Chlorella sorokiniana showing the strongest growth inhibition of the plant pathogen Phytophthora cactorum. Different pre-treatments like freeze-drying, solvents with different polarities, and extraction methods were analyzed in regards to the level of antimicrobial activity of C. sorokiniana. The best C. sorokiniana extract demonstrated potential for biopesticide application on strawberry leaves infected with P. cactorum. This study reveals the potential of microalgae as natural biopesticide for organic or more sustainable regular agriculture.